Social Status - Chaim Fershtman (Northwestern University, Kellogg School of Management, Center for Mathematical Studies in Economics and Management Science, 1993)
A common feature of recent growth models is the existence of externalities associated with human capital. Each worker, in choosing his level of schooling or occupation, ignores the impact of his choie on future generations. Thus, in general, the level of investment in human capital is suboptimal. One possible corrective mechanism is to reward investment in human capital with social status. As recognized by sociologists, the occupational social status is an important factor in occupational choice. The paper investigates the implications of social rewards onthe edistribution of talents in society and consequently on the process of economic growth. We consider two sources of heterogeneity among workers: non wage income and ability. We find that the thrive for status may be counter productive, inducing an inefficient allocation of talent. A greater emphasis on status may induce the "wrong" individuals i.e. those with low ability and high wealth to acquire schooling, causing workers with high ability but low wealth to leave the growth enhancing occupations. This crowding ou;effect, taken alone, discourages growth. In general, growth may be enhanced by an increase in the number of workers who invest in education. However, the inefficiency in the allocation of talent persists.
Keywords: 330